2015
DOI: 10.1002/art.38916
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral CD5+ B Cells in Antineutrophil Cytoplasmic Antibody–Associated Vasculitis

Abstract: Objective CD5+ B cells have been conceptualized as a possible surrogate for Breg cells. The aim of the present study was to determine the utility of CD5+ B cells as biomarkers in antineutrophil cytoplasmic antibody–associated vasculitis (AAV). Methods The absolute and relative numbers (percentages) of CD5+ B cells (explanatory variables) were measured longitudinally during 18 months in 197 patients randomized to receive either rituximab (RTX) or cyclophosphamide (CYC) followed by azathioprine (AZA) for the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 30 publications
2
15
1
Order By: Relevance
“…We found that the number of Bregs has no correlation with the number of neutrophils (data not shown), suggesting that our findings do not represent a general inflammatory response. Although previous studies have shown that the levels of CD5 + B cells and IL-10 + B cells are decreased in antineutrophil cytoplasmic antibody-associated vasculitis [ 38 41 ] and the frequency of IL-10–producing B cells is higher in hepatitis B virus-associated membranous nephropathy [ 42 ], our study is the first to indicate that CD38 + CD19 + B cells and Bregs may participate in the pathogenesis of HSPN.…”
Section: Discussioncontrasting
confidence: 57%
“…We found that the number of Bregs has no correlation with the number of neutrophils (data not shown), suggesting that our findings do not represent a general inflammatory response. Although previous studies have shown that the levels of CD5 + B cells and IL-10 + B cells are decreased in antineutrophil cytoplasmic antibody-associated vasculitis [ 38 41 ] and the frequency of IL-10–producing B cells is higher in hepatitis B virus-associated membranous nephropathy [ 42 ], our study is the first to indicate that CD38 + CD19 + B cells and Bregs may participate in the pathogenesis of HSPN.…”
Section: Discussioncontrasting
confidence: 57%
“…However, the predictive utility of measuring CD19 + CD5 + B cell numbers for assessment of disease relapse following either rituximab or conventional cyclophosphamide-based therapy was not validated in an analysis of data from the RAVE trial (3). In fact, the number of CD5 + B cells was found to be highly variable from the time of acute disease to remission and no association with subsequent relapses was observed (118). Paradoxically, clinical trials of B cell depletion agents have not demonstrated benefit in SLE (121,122).…”
Section: [H2] Kidney Transplantationmentioning
confidence: 99%
“…Furthermore, patients treated with rituximab who were on low or no maintenance immunosuppression and who had a low or sharply declining repopulation percentage of CD5+ B cells relapsed sooner than patients maintained on high maintenance immunosuppression (median 17 versus 29 months, respectively, P = 0.002). With the presumed intention of validating these findings, Unizony et al recently analyzed absolute and relative numbers of CD5+ B cells from PBMC samples collected from 197 participants in the RAVE trial over 18 months and were unable to identify a significant association with disease severity and/or failure of induction therapy; however, analytic methodologies may have been different [32]. CD5 is one of several cell surface markers that characterize regulatory B cells.…”
Section: Immune Cell Dysregulationmentioning
confidence: 99%